DESIGN AND BUILD CREDIT ANALYSIS APPLICATIONS FOR MULTI-FINANCE COMPANIES - Suwandi Suwandi; Gytha Nurhana; Wiwiek Nurkomala Dewi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The making of this credit analysis application is designed to facilitate the credit analysis team (financing company), so that it can assist company management in making decisions whether or not customers are eligible for credit facilities. Good or bad performance of companies engaged in credit, depends on the strength of credit analysts in analyzing potential customers. This research topic is very important for finance companies, considering that many finance companies are not careful in analyzing credit, so that it can result in high arrears. A high level of arrears can cause the company's profitability to decline, even loss. This study uses the 5-C analysis method, namely Character, Capacity, Capital, Collateral, Condition. While the procedure used in this study is to use the software development method with the Waterfall System Development Line (SDLC). This study aims to create an application that can be used by multi-finance companies in conducting credit analysis of prospective customers, using the 5C method. The result of this research is the formation of a web-based application that can be used to decide whether prospective customers deserve credit or not by using 5C analysis. With the creation of a computerized system in deciding whether or not prospective customers are given credit, of course, it is very helpful for company management (credit division) in analyzing credit. This of course can increase the productivity of the company, which in the end will affect the welfare of employees.